TANGGUNG JAWAB TRIDHARMA PERGURUAN TINGGI MENJAWAB KEBUTUHAN MASYARAKAT - Lian, Bukman (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Universities carry out the function of tridharma: education and teaching, research, and community service. The three dharma are interrelated, among others, the first dharma (education: theoretical) and second (research: innovation) must concretely support the third dharma (devotion: transformation). The research was conducted not only for the sake of the research itself, credit numbers, promotion, money. In carrying out the research contained an important mission, namely for the benefit of society. That is, the community remains a focus, especially in social research. So, the results and findings of the research must have a